Report of the Indian Famine Commission : 1880-1885 - India; Agricole Publishing Academy, New Delhi (New Delhi : Agricole Pub., 1989)
The document deals with all aspects of devastating famines to which the provinces of India had from time to time been liable directly to the occurrence of seasons of unusual drought, the faliure of the customary rain fall leading to the failure of food crops on which the subsistence of the population depends.
Pt. I -- Famine relief.- [2], iv, 69 p. -- pt. II -- Measures of protection and prevention - viii, 71-185 p. -- pt. III -- Famine histories - vii, 1-264 p.
Commission of Inquiry on Indian Famines, appointed by the Government of India, 16th May, 1878
The book divided in the 3 Parts.
Keywords: Famines -- India; India -- History -- Famine, 1880-1885